2015
DOI: 10.1038/mt.2014.222
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Silencing for the Treatment of Colitis: A Combined In Vivo Strategy Based on RNA Interference and Engineered Escherichia Coli

Abstract: Nonpathogenic-invasive Escherichia coli (InvColi) bacteria are suitable for genetic transfer into mammalian cells and may act as a vehicle for RNA Interference (RNAi) in vivo. Cyclooxygenase-2 (COX-2) is overexpressed in ulcerative colitis (UC) and Crohn's disease (CD), two inflammatory conditions of the colon and small intestine grouped as inflammatory bowel disease (IBD). We engineered InvColi strains for anti-COX-2 RNAi (InvColi(shCOX2)), aiming to investigate the in vivo feasibility of a novel COX-2 silenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…With the same purpose, L. lactis was also modified to secret IL‐10 and IL‐27 150,154. Other bacteria employed for this approach are genetically modified Bacteroides ovatus (B. ovatus) and non‐pathogenic invasive Escherichia coli (E. coli ), which contributed to treating IBD,146,151 colon cancer,152 or were used for vaccination153 in animal models successfully. In a clinical study, genetically modified L. lactis that secrets anti‐inflammatory cytokine IL‐10 has been packaged in enteric capsules for ulcerative colitis treatment; however, the study failed to pass Phase II in 2009 (NCT00729872).…”
Section: Technologies For the Local Oral Delivery Of Biological Drugsmentioning
confidence: 99%
“…With the same purpose, L. lactis was also modified to secret IL‐10 and IL‐27 150,154. Other bacteria employed for this approach are genetically modified Bacteroides ovatus (B. ovatus) and non‐pathogenic invasive Escherichia coli (E. coli ), which contributed to treating IBD,146,151 colon cancer,152 or were used for vaccination153 in animal models successfully. In a clinical study, genetically modified L. lactis that secrets anti‐inflammatory cytokine IL‐10 has been packaged in enteric capsules for ulcerative colitis treatment; however, the study failed to pass Phase II in 2009 (NCT00729872).…”
Section: Technologies For the Local Oral Delivery Of Biological Drugsmentioning
confidence: 99%
“…Cyclooxygenase-2 (COX-2) is an enzyme induced by proinflammatory cytokines including TNF-α and is overexpressed in the colonic mucosa of IBD patients (Singer et al, 1998). Using the two genes previously mentioned, non-pathogenic invasive E. coli was engineered to transfer anti COX-2 RNAi to silence the expression of this enzyme resulting in positive effects on DSS-induced colitis in mice (Spisni et al, 2015).…”
Section: Constitutive Systemsmentioning
confidence: 99%
“…On the other hand, we and others have repeatedly seen in experiments that control groups receiving mock vectors very often showed a difference to the groups receiving no treatment at all. It suggests that the vectors have an immunomodulatory effect (41)(42)(43). This is not a negative finding per se, but it complicates the design of experiments to prevent bias in interpretation (44).…”
Section: Alternative Gene Therapymentioning
confidence: 99%
“…The inflammatory process has several regulatory control points that can be blocked by small interfering RNA. In a recent study an Italian group showed that by inhibiting the production of cyclooxygenase-2 the colitis severity can be significantly reduced (41). Interfering RNA was produced by invasive Escherichia applied via enema.…”
Section: Rna Interference Using Bacteriamentioning
confidence: 99%